2021
DOI: 10.3390/cancers13112525
|View full text |Cite
|
Sign up to set email alerts
|

Murine Macrophages Modulate Their Inflammatory Profile in Response to Gas Plasma-Inactivated Pancreatic Cancer Cells

Abstract: Macrophages and immuno-modulation play a dominant role in the pathology of pancreatic cancer. Gas plasma is a technology recently suggested to demonstrate anticancer efficacy. To this end, two murine cell lines were employed to analyze the inflammatory consequences of plasma-treated pancreatic cancer cells (PDA) on macrophages using the kINPen plasma jet. Plasma treatment decreased the metabolic activity, viability, and migratory activity in an ROS- and treatment time-dependent manner in PDA cells in vitro. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 108 publications
(120 reference statements)
0
9
0
Order By: Relevance
“…Altered surface marker expression (Differentiation, maturation, and polarization ↑, pro-inflammatory phenotype tendency ↑) CC Direct: [ 117,57] (in vitro) Indirect: [49] (in vitro) [ 118,119,51] (in vivo) IC Direct: [ 109,113,115,118] (in vitro) Indirect: [ 110] (in vitro)…”
Section: Effect On Different Functions Of Macrophages and Dendritic C...mentioning
confidence: 99%
See 1 more Smart Citation
“…Altered surface marker expression (Differentiation, maturation, and polarization ↑, pro-inflammatory phenotype tendency ↑) CC Direct: [ 117,57] (in vitro) Indirect: [49] (in vitro) [ 118,119,51] (in vivo) IC Direct: [ 109,113,115,118] (in vitro) Indirect: [ 110] (in vitro)…”
Section: Effect On Different Functions Of Macrophages and Dendritic C...mentioning
confidence: 99%
“…Altered secretory profile (Pro-inflammatory tendency ↑) CC Direct: [ 117,57] (in vitro), [ 55,59] (in vivo) Indirect: [49] (in vitro) IC Direct: [ 109,113,115,118,120,57] (in vitro) Indirect: [ 110] (in vitro)…”
Section: Effect On Different Functions Of Macrophages and Dendritic C...mentioning
confidence: 99%
“…Miller et al [33] found that low-plasma-treated macrophages showed an increased migratory activity and mediated tumor cell killing in a TNF-α-mediated manner. Khabipov et al [34] studied plasma exposure of pancreatic ductal adenocarcinoma (PDA), and subsequent co-culture with macrophages significantly reduced the number of macrophage clusters compared to untreated PDA cells. Therefore, tumor therapy by targeting proinflammatory macrophages may become an attractive anti-tumor treatment strategy.…”
Section: Ltp Enhances the Anti-tumor Effects Of Macrophagesmentioning
confidence: 99%
“…Several studies have further focused on metabolic profiling via mass spectrometry ( 33 , 34 ) or positron emission tomography (PET) imaging for evaluation of glucose metabolism and protein synthesis ( 53 ). At the simplest, the metabolic activity can be assessed by conventional colorimetric or fluorescence-based methods, including resazurin, MTT, and WST assays before or after tumor dissociation ( 10 ). While non-malignant cells exhibit a limited number of divisions, cancer cells bypass this barrier by hijacking telomerases to extend the length of their telomeres.…”
Section: Introductionmentioning
confidence: 99%